Utility of Routine Esophageal Biopsies in Patients With Refractory Reflux Symptoms. (8th April 2021) - Oude Nijhuis, Renske A.B.; Curvers, Wouter L.; van der Ende, Mirjam; Herregods, Thomas V.K.; Schuitenmaker, Jeroen M.; Smout, Andreas J.P.M.; Bredenoord, Albert J.
Abstract : INTRODUCTION: This study aimed to assess the diagnostic yield of routine esophageal biopsies in patients with refractory reflux symptoms. METHODS: We prospectively enrolled consecutive patients referred for upper endoscopy and collected histological, clinical, and endoscopic data. RESULTS: Of the 301 included patients, 14 (4.7%) patients met the clinicopathological diagnostic definition of eosinophilic esophagitis. Presence of dysphagia, food bolus impaction, atopic background, and typical endoscopic features were the factors with the strongest association and diagnostic accuracy for eosinophilic esophagitis. The diagnostic yield in patients lacking symptoms of dysphagia or endoscopic features was negligible (0% and 1.9%, respectively). DISCUSSION: Routine esophageal biopsy sampling in patients with refractory reflux symptoms has a low diagnostic yield. Esophageal biopsies should only be obtained in patients with refractory reflux symptoms who also present with dysphagia (see Visual abstract, Supplementary Digital Content 2, http://links.lww.com/AJG/B792 ).